Kebijakan Kepala Sekolah dalam Mempertahankan Akreditasi A: Studi Kasus di SMP Islam Al Falah Kota Jambi - Murni, Putri; Jamaluddin, Jamaluddin; Istofa, Dian Nisa (Jurnal Pendidikan Madrasah, 2026)
This study examines the principal’s policy in maintaining an “A” accreditation status at SMP Islam Al Falah Kota Jambi. A qualitative descriptive approach was employed to explore the implementation of accreditation-related policies in depth. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using the Miles and Huberman interactive model, including data condensation, data display, and conclusion drawing. The findings reveal that the principal’s policy has been implemented consistently to sustain the “A” accreditation status. This is evidenced by stable accreditation outcomes and the application of the 2024 Institutional Accreditation (IA) instrument from BAN-PDM, covering teacher performance, school leadership, learning climate, and student achievement. Evaluation practices focus on teacher performance and school facilities monitoring. Supporting factors include strong institutional support, effective teamwork, and adequate infrastructure. However, challenges remain, particularly time constraints due to multiple responsibilities and high administrative workloads. To address these issues, the school applies task prioritization based on urgency and impact, simplifies administrative procedures, and promotes digitalization to improve efficiency and reduce redundancy in school management.